Lime and calcium-magnesium silicate in the ionic speciation of an Oxisol - Antonangelo, Joao Arthur; Ferrari Neto, Jayme; Costa Crusciol, Carlos Alexandre [UNESP]; Ferracciu Alleoni, Luis Reynaldo (Univ Sao Paolo, 2017)
Plant residues and certain fertilizers accelerate soil acidification and increase the levels of aluminum-Al+3 in soils under no-tillage (NT). Silicates act as acidity amendments and as a source of silicon as in H4SiO4. An increase in the pH of soil solution causes the deprotonation of H4SiO4 and generates the anionic form (H3SiO4-). The aim of this study was to evaluate the ionic speciation of Si, Al, Ca, Mg and K in aqueous extracts by means of a software calculation. Since 2006, a field experiment has been under way on an Oxisol under NT subjected to lime and calcium-magnesium silicate applications under four crop systems. The amendments were applied in Oct 2006 and in Oct 2011, aiming to raise base saturation to 70 %. Soil samples were collected in Oct 2013, at depths of 0-5, 5-10, 10-20, 20-40 and 40-60 cm. Both Ca and Mg formed complexes with dissolved organic carbon (DOC) whereas the same was not observed for potassium. These three basic cations were mostly in their free forms regardless of treatment, while Al was mostly complexed with DOC even at the lowest depths (40-60 cm). The highest value of free Al form was 15 %. Si was almost 100 % as H4SiO4, and its activity was similar to its concentration in solution for all crop systems and at all depths, regardless of amendment applied. The percentages of H3SiO4- and Al-H3SiO42+ were irrelevant, providing more phytoavailable H4SiO4 in soil solution.
Keywords: soil solution; cations speciation; aqueous extraction; amendments